Structure of an actively exchanging complex between carboxypeptidase A and a substrate analogue. - Rees, D C (1980)
An x-ray diffraction study at 2.8 A resolution has yielded the structure of a complex between bovine carboxypeptidase A (peptidyl-L-amino-acid hydrolase, EC 3.4.17.1) and (-)-2-benzyl-3-p-methoxybenzoylpropionic acid. This substrate is an analogue of N-(p-methoxy)-benzoylphenylalanine, in which the amide NH is replaced by CN2. T. Sugimoto and E T. Kaiser (1979) J. Am. Chem. Soc. 101, 39469--3951] have shown that this complex catalyzes stereospecific exchange of that proton of the CH2 group which is in the R configuration. Our structure of this complex suports the model proposed by Sugimoto and Kaiser and is very similar to the productive peptide binding mode suggested by Lipscomb et al. [Lipscomb, W. N., Hartsuck, J. A., Reeke, G. N., Quiocho, F. A., Bethge, P. A., Ludwig, M. L., Steitz, T. A., Muirhead, H. & Coppola. J. C. (1968) Brookhaven Symp. Biol. 21, 24--90]. The proposed roles of glutamic acid 270 in the proton exchange and the interaction of zinc with the carbonyl group of the substrate are consistent with the observed structure.